Elastic Band Training Effect to Parameters of Sarcopenia in Elderly Community-Dwelling - Vitriana Biben; Irma Ruslina Defi; Derry Suselo (Global Medical & Health Communication (GMHC), 2019)
Physiologically aging causes the decreased of muscle mass, strength, and or limited activity known as sarcopenia in the elderly. The decrease in muscle capacity occurs in all elderly, active, or sedentary. Exercise for the elderly is considered not enough to prevent the decrease of function that will occur. Therefore, it is necessary to add strength training to the elderly, such as elastic band exercise. The effect of strength training in 12 weeks with elastic band strengthening exercise on muscle mass, muscle strength, and physical performance as sarcopenia parameters measured in this study. The interventional study design was conducted in elderly community-dwelling in Bandung city, West Java, from May to July 2016. Thirty elderly (60–81 years old) muscle mass measured using bioelectrical impedance analysis (BIA), handgrip strength using hand dynamometer and walking distance as the parameter of physical performance, using 6-minute walking test. Significant differences found in hand muscle strength (p=0.007), walking distance (p=0.000) after elastic band strengthening exercise, but there were no significant changes in muscle mass (p=0.236) even though the muscle mass increased after 12 weeks of strengthening exercise. In conclusion, additional elastic band strength exercise for regular elderly exercise can increase muscle strength and physical performance. PENGARUH LATIHAN DENGAN PITA ELASTIK TERHADAP PARAMETER SARKOPENIA PADA USIA LANJUT DI KOMUNITASPenuaan secara fisiologis menyebabkan penurunan massa, kekuatan otot dan/atau keterbatasan aktivitas pada usia lanjut (usila). Penurunan kemampuan otot ini terjadi pada semua usila, baik yang aktif maupun nonaktif sehingga senam usila yang ada dianggap tidak mencukupi untuk mencegah penurunan fungsi yang akan terjadi. Oleh karena itu, diperlukan penambahan latihan kekuatan pada usila seperti latihan kekuatan menggunakan pita elastik. Penelitian ini bertujuan mengetahui pengaruh latihan kekuatan dengan pita elastik selama 12 minggu terhadap massa otot, kekuatan otot, dan performa fisik yang merupakan parameter sarkopenia pada usila. Desain penelitian intervensi dilakukan pada usila di komunitas Kota Bandung, Jawa Barat periode bulan Mei sampai Juli 2016. Sebanyak 30 partisipan (usia 60–81 tahun) diukur massa otot menggunakan bioelectrical impedance analysis (BIA) dan kekuatan otot menggunakan dinamometer tangan, serta uji jalan 6 menit untuk mengukur performa fisik. Perbedaan bermakna ditemukan pada kekuatan otot tangan (p=0,007) dan jarak tempuh jalan (p=0,000) setelah dilakukan latihan kekuatan dengan pita elastik, tetapi tidak didapatkan perbedaan bermakna pada massa otot tangan dan kaki (p=0,236) walaupun terjadi peningkatan massa otot setelah dilakukan latihan selama 12 minggu. Simpulan, penambahan latihan kekuatan dengan pita elastik pada program senam usila meningkatkan secara bermakna kekuatan otot dan performa fisik usila.